ANALISIS PENGARUH CORPORATE GOVERNANCE, INTERNAL CONTROL DAN ADOPSI PSAK 109 TERHADAP KINERJA OPZIS DIY MELALUI METODE BALANCE SCORECARD - Sulastiningsih Sulastiningsih; Khalida Urfiyya (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2019)
The purpose of the research is to measure the performance of zakat management organizations (OPZIS) in Yogyakarta using balance scorecard methode, also to analyze and determine the effect partially and simultaneously on the Corporate Governance, Internal Control and the adoption level of PSAK 109 to OPZIS performance. The object of this study using four OPZIS in Yogyakarta included into the members of Indonesia Zakat Forum (FOZ). This research method used scoring technique on balance scorecard performance and multiple linear regression analysis with SPSS 23.00 which is used to see the influence of the independent variable in the form of corporate governance, internal control and adoption level of PSAK 109 to OPZIS performance. The results of this research shows that OPZIS performance measuremnt using the balanced scorecard method had an average score of 3.55 which maximized the category quite well. Based on F test, independent variable has an effect on OPZIS Performance, shown with F value equal to 6,080 and significance equal to 0.002, overall independent variable are able to explain the effect about 22.437%. While based on partial t test, showed that the adoption level of PSAK 109 has a significant negative effect. Meanwhile, corporate governance and internal control have no effect on OPZIS performance through balance scorecard method.